Digitalisasi Bisnis Dan Inklusi Keuangan Sebagai Upaya Mendorong Kinerja Umkm Melalui E-Commerce Di Era Digital - Uum Helmina Chaerunisak; Sri Ayem; Septiana Wahyu Prasetyaningtyas; Riska Widya Afrianingrum; Naresha Hanun (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
Micro, Small and Medium Enterprises (MSMEs) are creative industries that rely on the ideas of their owners and currently play an important role in the Indonesian economy. The performance of MSMEs in Indonesia has progressed and developed in recent years. financial inclusion and digital business are two important things. They complement each other and have the potential to improve the performance of MSMEs. Financial inclusion can provide MSMEs with access to financial products and services such as insurance credit and pension funds. Digital business can help MSMEs to expand their market, improve operational efficiency and increase marketing effectiveness. Therefore, financial inclusion and digital business can help MSMEs to increase productivity efficiency and competitiveness. In improving its performance in line with financial inclusion and digital business, the use of shopee for the MSME community must be in line with the times and follow information technology which aims to expand the market and increase sales. To determine whether digital business and financial inclusion have a significant impact on MSME performance, the study reviewed some previous research or used systematic literature review methods. We used secondary data from Google Scholar articles published between 2019 and 2024. The results showed that digital business and financial inclusion have a positive effect on the performance of MSMEs. However, the study (Ruli et al., 2021) argues that financial inclusion does not have any effect on the performance and sustainability of the MSME sector, which is contrary to this.